Pemanfaatan multimedia interaktif berbantuan komputer dengan aplikasi Macromedia Flash 8 untuk meningkatkan hasil belajar Biologi - Komariah Komariah (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
This study investigated the efficacy of using classroom action research methodologies to improve student learning outcomes in class VIII SMP. Planning, implementation, observation, and reflection are the four steps of the method. The results obtained after the action showed an increase in student involvement and response in the teaching and learning process, with observations in each cycle indicating that the number of students whose level of activity/interest in learning was in ”good” category was 61.1% in the first cycle and increased to 91,7% in the second cycle. The increase in learning outcomes was significant, as evidenced by the average value before the action, which increased by 44.62 in the first cycle, namely to 67.12 after the action was carried out, and students who completed the KKM were 17 people (65.38%), whereas in the second cycle, the average score of 66.9 before the action becomes 78.1 after the action, with students completing above the KKM being 23 people, and at the end of this second cycle, classically, it has risen to the impact of computer-assisted interactive multimedia learning with the Macromedia Flash 8 program is increased activity and better student learning results. This study recommends to improve student learning outcome by applying interactive multimedia learning with the Macromedia Flash 8 program.